The Anatomy of Japanese Business. - Sato, Kazuo (Taylor & Francis, 2010)
This volume collects eleven essays written by Japanese experts on various aspects of Japanese business management and is a sequel to the volume ""Industry and Business in Japan"". It examines the mechanisms for Japan's phenomenal economic growth since the Second World War by analyzing Japanese management, business groups, production systems and business strategy.